The image of the manager-leader of the near future - an outline of the issues = Wizerunek menedżera-przywódcy niedalekiej przyszłości - zarys problematyki - Glinkowska, Beata; Kaczmarek, Bogusław (Zielona Góra: Faculty of Economics and Management Press)
The study contains description characteristics and analyses (obviously abbreviated) of two approaches and two concepts of management regarding the manager-leader of the near future. The first concept refers to new tasks and skills of the manager-leader. The second concept concerns the nature of the so-called manager of tomorrow, called - although it is not yet common name in management - the manager - eco-leader.
Keywords: menedżer; menedżer jutra; menedżer-przywódca; eco-menedżer; organizacja; przedsiębiorstwo; manager; manager of tomorrow; manager-leader; eco-manager; organization; company; near future